New species of Donda Moore, 1882 and new data on Pantheinae species. Revision of Pantheinae, contribution XIV (Lepidoptera, Noctuidae: Pantheinae) - Han, H.l.; Behounek, G.; Kononenko, V.s. (Zootaxa, 2020)
This paper supplements earlier revisions and descriptions of the subfamily Pantheinae (Behounek et al. 2012a, 2012b, 2015a, 2015b; Behounek and Kononenko 2012a, 2012b. It contains the description of Donda hunana sp. n., description of the male of Anabelcia thai Behounek & Kononenko, 2012 which was described from a small series of females, and new data on distribution of Xizanga mysterica Behounek, Han & Kononenko, 2012b and Pantheaforma ihlei Behounek, Han & Kononenko, 2015a.